Dampak Pelatihan dan Pengembangan, Kepuasan Kerja, Kompensasi terhadap Retensi Karyawan - Mutiara Sapitri; Agung Sedayu; Diana Aqmala; Adilla Kustya Ulfa (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the influence of training and development, job satisfaction, and compensation on employee retention. The research employs a quantitative approach by distributing questionnaires as a data collection technique. The sampling method used is a census sampling technique, with a total of 87 respondents who are employees of PT Kuangyu Motors. The data analysis technique involves multiple linear regression analysis using IBM SPSS Statistics software. The results indicate that job satisfaction has a positive and significant effect on employee retention, whereas training and development, as well as compensation, do not have a significant impact on employee retention at PT Kuangyu Motors.  Keywords: Training And Development, Job Satisfaction, Compensation, Employee Retention